The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fphar.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Mainstream Medications for Patients With cDMARD-Naïve Rheumatoid Arthritis: A Network Meta-Analysis

Abstract: Background: The mainstream medications for rheumatoid arthritis (RA) include conventional disease-modifying antirheumatic drugs (cDMARDs), which mostly are methotrexate (MTX), and biologic agents such as adalimumab (ADA), certolizumab (CZP), etanercept (ETN), golimumab (GOL), infliximab (IFX), and tocilizumab (TCZ). This network meta-analysis was aimed at evaluating the efficacy and safety of the medications above and interventions combining cDMARDs and biologic agents for patients with RA.Methods: PubMed, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…In this study, the retention rate of TCZ was high in all age groups, particularly in patients aged <65 years, and remained high in those aged ≥65 years. In a meta-analysis of studies on RA, TCZ and MTX combination was identi ed as the best intervention [37]. TCZ showed higher retention rates than TNFi and ABA in other studies [38,39], which supports the results of this study.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the retention rate of TCZ was high in all age groups, particularly in patients aged <65 years, and remained high in those aged ≥65 years. In a meta-analysis of studies on RA, TCZ and MTX combination was identi ed as the best intervention [37]. TCZ showed higher retention rates than TNFi and ABA in other studies [38,39], which supports the results of this study.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the fact that several trials and meta-analyses have demonstrated that efficacy outcomes improve when using tumour necrosis factor inhibitor (TNFi) bDMARDs as first-line treatment41 42 they have poor cost-effectiveness profiles 43 44. One of the challenges with these earlier analyses is that prices from before the approval of biosimilar TNFis were used for cost-effectiveness calculations.…”
Section: Discussionmentioning
confidence: 99%
“…While the benefit of immediate infliximab in preventing joint damage has been shown over other treatment strategies [15,34], radiographic progression was out of the scope of this review. Several other recent meta-analyses have compared the combination of biologic agents plus MTX over csDMARDs in early MTX-naïve RA [3, [17][18][19]64] [17] included 20 RCTs in the analysis of ACR20, ACR50 and ACR70 endpoints. In one of the five included infliximab studies, all patients received three months of MTX induction therapy before randomization [17].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Several other recent meta-analyses have compared the combination of biologic agents plus MTX over csDMARDs in early MTX-naïve RA [3, [17][18][19]64] [17] included 20 RCTs in the analysis of ACR20, ACR50 and ACR70 endpoints. In one of the five included infliximab studies, all patients received three months of MTX induction therapy before randomization [17]. Stevenson et al [64] in a comprehensive HTA report commissioned by NICE, synthesized month 6 ACR and EULAR response outcomes for seven biological drugs, including two infliximab trials.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation